Identification of Pakistani Isolates of Xanthomonas oryzae pv. oryzae by Insertion Sequence based polymerase chain reaction (IS-PCR) - Mannan, Shazia; Hameed, Shahid (Journal of Phytology, 2013)
Xanthomonas oryzae pv. oryzae is the causal agent of bacterial blight disease in rice. The pathogen was isolated from infected samples collected after extensive survey of rice growing areas of Pakistan. Afterwards, Insertion sequence based Polymerase chain reaction was applied using the high copy insertion sequence IS1113 based primer for molecular identification of the isolates as well as to differentiate them from Xanthomonas oryzae pv. Oryzicola